2019
DOI: 10.1155/2019/1340934
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Failure Modes of Rock Specimens with Specific Joint Geometries in Triaxial Unloading Compressive Test

Abstract: The effects of disconnected joints on the mechanical characteristics of rock masses are interesting and challenging aspects of rock mechanics. The prime objective of this study is to investigate the effect of joint orientations and joint connectivity rates on the strength, deformation, and failure mechanisms of rock specimens under unloading condition. To establish the relationships between different factors (confining pressure, joint orientation, and joint connectivity) and failure mechanisms, a series of tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…During the loading process of the rock, with the internal damage, the elastic energy stored will exceed its bearing limit and be released suddenly, leading to instantaneous failure of the rock. Part of the released elastic energy is used for the fracture of the rock, that is, the postpeak failure energy U f , which is calculated by Formula (10); the other part is the surplus energy U y , which is mainly the initial kinetic energy used for rock failure ejection. e calculation method is shown in Formula (11) [34].…”
Section: Analysis On Energy Conversion Of Sandstone Under Unloading Cmentioning
confidence: 99%
See 1 more Smart Citation
“…During the loading process of the rock, with the internal damage, the elastic energy stored will exceed its bearing limit and be released suddenly, leading to instantaneous failure of the rock. Part of the released elastic energy is used for the fracture of the rock, that is, the postpeak failure energy U f , which is calculated by Formula (10); the other part is the surplus energy U y , which is mainly the initial kinetic energy used for rock failure ejection. e calculation method is shown in Formula (11) [34].…”
Section: Analysis On Energy Conversion Of Sandstone Under Unloading Cmentioning
confidence: 99%
“…Guo et al [8] theoretically studied the evolution of the mechanical properties of the rock mass under the unloading state from the perspective of elastic strain energy. Li et al [9,10] conducted an unloading test on the rock mass containing joints, and discussed the impact of joint inclination angle on the mechanical properties of the rock sample. Regarding the research on rock deformation and dilatancy under the unloading effect, Yang et al [11,12] carried out the unloading test on transversely isotropic rock mass, and investigated the influence of parallel schistosity and vertical schistosity on the deformation and dilatancy of rock samples.…”
Section: Introductionmentioning
confidence: 99%
“…At present, seismic research on special geological structures still focuses on seismic parameter research [20], with little consideration of the special shape of the structure [21]. The existing literature [22][23][24] on jointed rock masses mainly studies the influence of geometric parameters, including the inclination angle [25], length, and connectivity rate [26], on the mechanical properties of rock masses. There are few joint studies on the inclination angle changes.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of forming a new stress equilibrium environment, the load of ore rock on working surface increases and decreases. Based on this, scholars believe that the deformation law of rock in the unloading process is of more engineering practice significance, so the mechanical test of deep rock during unloading was carried out by them [19][20][21][22]. For example, by studying the mechanical characteristics of deep rock considering prepeak unloading damage, it is found that the static and dynamic macroscopic mechanical parameters of the rock decrease with the increase of damage variables, and the final failure mode of the rock also shows some differences when the unloading rate is different [23][24][25].…”
Section: Introductionmentioning
confidence: 99%